Principles of Caution by Land Deed Officials (Ppat) in Transfer of Land Rights - Prastowo, Novarisma Listiarini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The deed of land right transfer is a valid evidence instrument created by the Land Deed Official (PPAT) as an authorized official, which provides legal certainty and protection to the parties regarding the transfer of land ownership. However, a land transfer deed for uncertified land is prone to disputes if the PPAT does not apply the principle of prudence. Therefore, this research aims to analyze the application of the PPAT's principle of prudence in the sale and purchase of land rights, focusing on the case study of Decision Number: 712/Pdt.G/2022/PN.Tng, and to analyze the legal protection for the buyer of land rights without title documentation. The method used in this research is normative juridical, utilizing primary, secondary, and tertiary data sources obtained from literature study. The collected data will then be analyzed and systematized qualitatively. The results of this study indicate that, firstly, the PPAT has not applied the principle of prudence as they were deemed insufficiently thorough in ensuring the validity of the data during the creation of the deed. The second finding shows that a buyer of land rights whose ownership is not proven in court is considered illegitimate, thus the buyer does not obtain legal protection. However, the buyer can pursue legal remedies such as appeal, cassation, and judicial review.